Analisis dan Perancangan Sistem Informasi Perpustakaan Berbasis Website - Ahmad Alfin Hidayat; Andi Setiawan Prakoso; Putra Panglima Perkasa (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
As part of an educational institution, the school library is obliged to provide all sources of information needed for the education and learning process. In order to improve the service of library information resources, an information system is needed that makes services more effective and efficient. The research method used is a system development method, namely building a new system in the school library or developing an existing system. The design of the school library information system is based on a needs analysis that aims to reduce the difficulties encountered in library services. The school library's information system is simpler than that of a university library or district library, and is based on lending services such as loan/return and detailed notification. This school library information system was developed using the phpMyAdmin programming language and SQL database. The steps taken include collecting data collected, member data, printing member cards, printing cards without a library, borrowing and returning transactions, and data reports including detailed reports. The design carried out to create a school library information system includes system design to interface design that aims to make it easier for users and staff to manage school library management. It is hoped that with a simple system design, each school library can create its own information system for the library so that library services are more effective.